The SAGE Handbook of Sociolinguistics 2011
DOI: 10.4135/9781446200957.n39
|View full text |Cite
|
Sign up to set email alerts
|

Language, Migration and Human Rights

Abstract: They should have just taken a gun and shot my son": Taser deployment and the downtrodden in Canada. Social Identities: Journal for the Study of Race, Nation and Culture, 18, 65-83. Palys, T. (2008). When does Taser use become torture? Submission to the Thomas R. Braidwood, QC, Study Commission on Police Use of Conducted Energy Weapons in British Columbia. Retrieved from http://www.sfu.ca/~palys/articles.htm Piller, I., & Takahashi, K. (2011). Language, migration, and human rights. In R. Wodak, B. Johnstone, & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Culturism is a form of Orientalism (Said 1978 ), an ideology that serves to justify colonial and neocolonial relationships. As explicit racism has largely become unspeakable in mainstream North America and Europe (Piller and Takahashi 2011 ), invoking " their culture " has often served to cloak discrimination. Conversely, minority groups may actually rally around cultural identity in order to escape being racially framed, as is, for instance, the case for the Indian community in the USA.…”
Section: Inequality In Intercultural Communicationmentioning
confidence: 99%
“…Culturism is a form of Orientalism (Said 1978 ), an ideology that serves to justify colonial and neocolonial relationships. As explicit racism has largely become unspeakable in mainstream North America and Europe (Piller and Takahashi 2011 ), invoking " their culture " has often served to cloak discrimination. Conversely, minority groups may actually rally around cultural identity in order to escape being racially framed, as is, for instance, the case for the Indian community in the USA.…”
Section: Inequality In Intercultural Communicationmentioning
confidence: 99%
“…As this is also the best-educated generation of migrants ever with on average higher levels of English language proficiency than ever before (proficiency in English is an admission criterion for skilled migrants; many migrants are people who change their visa status from overseas student to permanent resident and thus have a degree from a local university), their lack of economic convergence flies in the face of the assumption that linguistic assimilation is a key facet of social inclusion. Consequently, a number of researchers have suggested that the demand for linguistic assimilation can sometimes become a smokescreen for racial discrimination (Colic-Peisker 2005;Colic-Peisker andTilbury 2006, 2007;Hill 2008;Lippi-Green 1997;Piller and Takahashi 2011). In contexts with policies of multiculturalism, and anti-racism and anti-discrimination legislation, language proficiency can become a supposedly neutral and objective indicator of individual worth and capacity.…”
Section: Social Inclusion and Linguistic Assimilationmentioning
confidence: 99%
“…The acquisition of language proficiency is apparently frequently perceived as being solely in the interests of migrants and not also in the interests of the host country, as well as being the host country's responsibility. Moreover, many politicians still have to be convinced that second language acquisition depends on the availability of professional teachers, good teaching materials and sufficient competence in one's native language (see Leung 2010; Piller & Takahashi 2010). Acceptance of, and respect for, migrants’ identities are important preconditions for second language acquisition and integration.…”
Section: Discussionmentioning
confidence: 99%